Marx e Machiavelli: politica, popolo e immanenza - Frosini, Fabio (Bollettino Filosofico, 2025)
A brief overview of the presence of the Marx-Machiavelli connection in Italian philosophical culture emphasises the importance of Antonio Gramsci’s suggestion that Machiavelli was the first proponent of the idea that politics is a science and an art that the subaltern classes should be interested in acquiring. This idea is employed to reconstruct Marx’s actual study of Machiavelli. Beyond general references, evidence of this can be found in two sets of notebooks dating from 1843 and 1852. These contain extracts from several of Machiavelli’s works, particularly the Discorsi sopra la prima deca di Tito Livio, organised in a way that reflects Marx’s interest in the Machiavellian concept of the “people” and its contradictory relationship with power. Keywords: Immanence, Machiavelli, Marx, People, Politics